Risk to plant health of Flavescence dorée for the EU territory. (9th December 2016) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Plant Health (PLH) performed a quantitative analysis of the risk posed by the Flavescence dorée phytoplasma (FDp) in the EU territory. Three scenarios were analysed, one with current measures in place (scenario A0), one designed to improve grapevine propagation material phytosanitary status (scenario A1) and one with reinforced eradication and containment (scenario A2). The potential for entry is limited, FDp being almost non‐existent outside the EU. FDp and its major vector, Scaphoideus titanus, have already established over large parts of the EU and have the potential to establish in a large fraction of the currently unaffected EU territory. With the current measures in place (A0), spread of FDp is predicted to continue with a progression of between a few and ca 20 newly infested NUTS 2 regions during the next 10 years, illustrating the limitations of the current control measures against spread. FDp spread is predicted to be roughly similar between scenarios A1 and A2, but more restricted than under scenario A0. However, even with reinforced control scenarios, stabilisation or reduction in the number of infested NUTS 2 regions has only relatively low probability. Under scenario A0, FDp has a 0.5–1% impact on the overall EU grapes and wine production, reflecting the effectiveness of the current control measures against impact. Under both scenarios A1 and A2, FDp impact is predicted to be reduced, by approximately one‐third (A1) to two‐thirds (A2) as compared to A0, but the associated uncertainties are large. The generalised use of hot water treatment for planting material produced in infected zones has the most important contribution to FDp impact reduction in scenario A1 and has high feasibility. Both increased eradication and containment measures contribute to impact reduction under scenario A2 but the overall feasibility is lower.